Cervical Cancer Screening: Assessment of Perception and Utilization of Services among Health Workers in Low Resource Setting - C. C. Ifemelumma; C. C. Anikwe; B. C. Okorochukwu; F. A. Onu; J. A. Obuna; B. N. Ejikeme; O. P. Ezeonu (Hindawi Limited, 2019)
Background. Cervical cancer is a preventable disease and the most common cancer among women in Nigeria. Objectives. To appraise the perception and utilization of cervical cancer screening services among female nurses in Federal Teaching hospital, Abakaliki. Materials and Methods. A cross-sectional study was done using semi-structured questionnaires on 408 consenting female nurses. Data was represented using simple percentages, charts, and Chi-square. Results. Of the 408 questionnaires shared, 388 were correctly and completely filled and analyzed. The respondents in this study showed good knowledge of cervical cancer as all (388) were aware that cervical cancer is a preventable disease of public health concern. Majority of them, 179 (46.1%) were between 21 and 30 years of age. The most common symptom of cervical cancer identified was postcoital bleeding (57%). Nursing training was the most common (73.5%) source of cervical cancer information. Utilization of cervical cancer screening was poor in this study as only 20.6% of the respondents had ever undergone screening. The most common reason for nonscreening was that they have not thought of it (28.4%). Conclusion. Despite the high level of awareness of cervical cancer screening, utilization remains low. There is, therefore, the need for cervical cancer education for the nurses to help improve utilization.